Optimization strategies for metabolic networks - Domingues, Alexandre (2010)
The work reported in this paper was performed within the project DynaMo - Dynamical modeling, control and optimization of metabolic networks, supported by FCT (Portugal) under contract PTDC/EEA-ACR/69530/2006.